Institutional Variations in Faculty Demographic Profiles - Mwenifumbo, Lorraine; Renner, K. Edward (Canadian Journal of Higher Education, 2017)
This paper proposes that many of the academic, financial and management challenges facing higher education are the result of a group of inter-related financial and demographic variables which are combining to produce a "ratchet" effect. Each twist of the ratchet reduces the institutional flexibility necessary for making adaptive responses with respect to revenue and expenses, renewal, and diversity which are required to avoid a further tightening of the ratchet. Another decade of decline may be ahead for Canadian Universities unless the dynamic interplay of the variables responsible for the ratchet can be reversed. Toward this end, the methodology of "institutional variations" is proposed, and is illustrated through an analysis of the faculty demographic profiles of nine Canadian universities. The proposed methodology requires focusing on collecting specific, descriptive information about individual institutions, rather than the usual strategy of collecting normative, aggregated information about higher education in general.